Sporolactobacillus—a new functional genus with potential applications - Xinyu Guo; Leilei Yu; Meifang Xiao; Xiaojie Zang; Chengcheng Zhang; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Current Research in Food Science)
Sporolactobacillus is a genus of lactic acid bacteria, which can be widely found in soil. According to NCBI, only 20 strains of the genus Sporolactobacillus have been identified through phenotypic and genotypic analysis, indicating their relatively low numbers compared to other lactic acid bacteria. Currently, there is a growing interest in isolating and studying Sporolactobacillus, particularly focusing on its physiological characteristics and conducting in vitro experiments. This paper provides a review of the sources and physiological characteristics of Sporolactobacillus, along with genotype analysis, carbohydrate metabolism traits, and potential antibacterial properties. It also delves into basic physiological characteristics, lactic acid production, and applications, offering insights for the future utilization of Sporolactobacillus and laying a foundation for exploring its potential applications.